THE EFFECT OF SELF ASSESSMENT SYSTEM IMPLEMENTATION ON TAXPAYER COMPLIANCE (A CASE STUDY OF INDIVIDUAL TAXPAYERS WITH FIXED INCOME (CIVIL SERVANTS) AT UNIVERSITAS NEGERI GORONTALO) - Ainun Nisa Putri Musa; Hartati Tuli; Siti Pratiwi Husain (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine the effect of the implementation of the Self Assessment System on the compliance of individual taxpayers with fixed income (civil servants) at Universitas Negeri Gorontalo. The method used in this study is a quantitative method using primary data obtained through the distribution of questionnaires to respondents who are Civil Servants (PNS) within the Universitas Negeri Gorontalo. The measurement of variables in this study used a Likert scale. The number of samples in this study was 93 respondents who were selected as the research objects. The data analysis techniques used in this study include validity test, reliability test, classical assumption test, simple linear regression analysis, t-test (partial), and coefficient of determination (R²), which were processed using the SPSS program. Based on the results of the study, it shows that the implementation of the Self Assessment System has a positive and significant effect on the compliance of individual taxpayers with fixed income (civil servants) at Universitas Negeri Gorontalo. This is evidenced by the results of the t-test which show a t-value of 17.783 with a significance level of 0.000 which is smaller than 0.05. In addition, the coefficient of determination (R²) value of 0.790 indicates that 79% of the variation in taxpayer compliance can be explained by the Self Assessment System variable, while the remaining 21% is influenced by other variables outside the research model.